Identification of key genes associated with perineural invasion in stage II colorectal cancer and their prognostic implications - Chang, Chen; Zhang, Bin; Chen, Jingli; Wang, Guorong (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to identify key genes associated with perineural invasion (PNI) in stage II colorectal cancer (CRC) and develop a prognostic nomogram. The goal was to create a model for more precise prognosis assessment and to guide personalized treatment for stage II CRC patients with PNI.MethodsBioinformatic analysis of The Cancer Genome Atlas (TCGA) database was used to identify differentially expressed genes (DEGs) associated with PNI in stage II CRC. Kaplan-Meier and Cox regression analyses identified prognostic genes for overall survival (OS). These genes, along with clinical factors, were integrated into a nomogram. The model’s performance was evaluated using calibration curves, receiver operating characteristic (ROC)/area under the curve (AUC) analysis, and decision curve analysis (DCA). Key gene expression in CRC tissues was validated by immunohistochemistry (IHC) and correlated with clinicopathological parameters.ResultsWe identified 33 DEGs associated with stage II CRC and PNI. High expression of CLDN18 and FTCD were independent poor prognostic indicators. A nomogram incorporating these genes and clinical factors accurately predicted 1-, 3-, and 5-year overall survival (OS), with AUC values exceeding 0.7. Calibration curves and DCA confirmed the model’s clinical utility. Immunohistochemistry (IHC) revealed that Claudin 18 protein expression was significantly higher in PNI-positive CRC tissues (P < 0.05) and correlated with age and lymphatic invasion (P < 0.05).ConclusionWe developed a novel prognostic nomogram for stage II CRC patients with PNI. This model provides a new tool for CRC prognosis, deepens the understanding of PNI pathogenesis, and helps identify therapeutic targets like Claudin 18, whose expression was confirmed as a potential biomarker. This tool can enhance personalized treatment strategies for this high-risk patient population.